1979
DOI: 10.1128/aem.37.3.496-504.1979
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium botulinum growth and toxin production in tomato juice containing Aspergillus gracilis

Abstract: The ability of spores of one type A and one type B strain of Clostridium botulinum to grow and produce toxin in tomato juice was investigated. The type A strain grew at pH 4.9, but not at pH 4.8; the type B strain grew at pH 5.1, but not at pH 5.0. Aspergillus gracilis was inoculated along with C. botulinum spores into pH 4.2 tomato juice; in a nonhermetic unit, a pH gradient developed under the mycelial mat, resulting in C. botulinum growth and toxin production. In a hermetic unit, mold growth was reduced, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…This effect was also seen with Rhizoctonia at day four, but no gradient in pH was found with Altemaria. Similar gradients have been observed in inoculated, sterilized tomato juice (Huhtanen et al, 1976;Odlaug and Pflug, 1979).…”
Section: Results and Discussion Development Of Lesions And Visual Appeasupporting
confidence: 82%
See 2 more Smart Citations
“…This effect was also seen with Rhizoctonia at day four, but no gradient in pH was found with Altemaria. Similar gradients have been observed in inoculated, sterilized tomato juice (Huhtanen et al, 1976;Odlaug and Pflug, 1979).…”
Section: Results and Discussion Development Of Lesions And Visual Appeasupporting
confidence: 82%
“…These observations lead to speculation that a metabiotic association may occur in fresh tomatoes involving molds and C. botulinum. Such a relationship has been observed in test tube studies with heated juice (Hutanen et al, 1976;Odlaug and Pflug, 1979). Therefore, this study was undertaken to determine whether growth of fungi in fresh tomatoes could create a situation in which C. botulinurn or C. sporogenes could grow in the fresh fruit and to determine if C. botulinurn could produce toxin in a metabiotic relationship with the fungi.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In a detailed study of the growth of Cl. botulinum in tomato juice, Odlaug & Pflug (1979) found that type A could grow and form toxin at pH 4.2 in tomato juice if Aspergillus gracilis was inoculated together with Cl. botulinurn.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of commercially processed tomato juice increased by an average of 2AE3 units (mean pH 6AE4) from an initial pH of 4AE1 when juice was inoculated with proteolytic fungi. Other researchers have observed that fungi commonly involved in spoilage of tomatoes are capable of raising the pH of tomato juice and tissue to levels that enable Clostridium botulinum to grow (Huhtanen et al 1976;Mundt 1978;Odlaug and Pflug 1979;Draughon et al 1988).…”
Section: Introductionmentioning
confidence: 99%